PROBLEMS FACED BY SECONDARY SCHOOL STUDENTS IN LEARNING MATHEMATICS: A CASE STUDY - Haokip, Alphonsa; Saroh, Dr.Tayum (IJRDO- Journal of Educational Research, 2022)
The purpose of this study is to see if secondary school students have any problems with learning mathematics and, if so, what the causes are. A total of 150 students were involved in the study, which was a descriptive case study based on qualitative understanding from three selected secondary schools, of which 50 were from St. Andrew’s School, 50 from St. Christopher’s School, and 50 from St. Mathew’s School. About 14% of the participants said they had no problems with learning mathematics, whereas 86 % said they had faced problems in learning the subject. The content analysis method was used to determine the causes of their learning problems, taking into account the type of problems they faced and the type of secondary school they attended. The findings suggested that the problems faced by the participants in learning mathematics were due to the teachers and the content. The students of St. Andrew’s school and St. Christopher’s school lamented that their learning problems were mainly teacher-based, while the students of St. Mathew’s school attributed their learning problems to contend-based. The findings of this study are expected to lessen the difficulties that secondary school pupils confront in their academic journey of learning mathematics.